Psychiatrische Erkrankungen in Schwangerschaft und Stillzeit: Häufigkeit, Verlauf und klinische Diagnostik = Mental disorders in pregnancy and postpartum : prevalence, course, and clinical diagnostics - Kühner, Christine (Der Nervenarzt, 2016)
The peripartum period represents a critical phase for the onset and course of mental disorders. During this phase, mental disorders occur as first onset or, more often, as recurrent or ongoing chronic conditions with onset and further course of illness in- or outside the peripartal period. No clear risk increase exists for the more prevalent mental disorders such as depressive and anxiety disorders during this period, whereas there is an increased risk for bipolar disorder. Peripartal mental disorders may impact fetal and child development through different mechanisms. The International Statistical Classification of Diseases and Related Health Problems (ICD-10) does not sufficiently take into account particularities of peripartal disorders with possible prognostic relevance. The present article gives an overview on prevalence, course, and clinical diagnostics and presents a proposal for consistent categorization of peripartal mental disorders.